Pengawasan Dalam Pengadaan Barang Dan Jasa: Optimalisasi Peran Pejabat Pembuat Komitmen Kementerian Perhubungan - M Arkansyah; Ida Nadirah; Cakra Arbas (Jurnal Bedah Hukum, 2023)
The issuance of Presidential Regulation Number 12 of 2021 concering a a Government Procurement of Goods/Services and its amendments have strengthened the existence of the Commitment Making Officer (PPK) as one of the state financial management officias who has a very large role and task. Given the importance of the role of PPK in the framework of the imolementation, of course it is necessary to omprove and at the same time reorganize its central role in order to improve the quality of services that are more excellentin in line with the increasingly complex demands of modern era developments. The purpose of this study was to find out about the legal arrangements regarding the role of officials making commitments in the implementation of goods and services procurement services at the Ministry of Transportation and knowing the role of commitment officials in implementing goods and services procurement services at the ministry of transportation and knowing the obstacles faced by commitment officials in impelemnting propcurement services. Goods and services at the ministry of transportation. The research method used in this study is research with an empirical juridical approach, where data is taken directly and literally from interviews and literature studies The results of research on legal arrangements regarding the procurement of goods and services in the Ministry of Transportation refer to the civil Code concerning cintracts, Law Number 2 of 2017 concerning contracts, Law number 2 of 2017 concerning Construction Services, Article 1number 10 and number 11 Law Number 1 of 2004 concerning State treasury. Presidential Regulation 54 of 2010, Presidential Regulatin 54 of 2010, Presidential Decree NO. 16 of 2018. The role of Commitment making officials in the procurement of goods ans services establishes plans for the implentation of goods/services procurement, signs contracts, executes contracts with goods and services providers and the obstacles faced by commitment officers in being accountable for goods procurement and services consisting of external obstacles, which are influenced by natural factors, while the internal obestacles to work must be in accordance with the aircraft departure schedule, implanting technical personel are not always in the field, implementing contractors are inexperienced in working on airport runway overlays so that performance is not optimal. This resulted in the committee making officials and consultants/implemenethers having to carry out maximum supervision.